Eating the messenger (RNA): autophagy shapes the cellular RNA landscape. (1st September 2021) - Kumaran, Girishkumar; Michaeli, Simon
Abstract : This article comments on: Hickl D, Drews F, Girke C, Zimmer D, Mühlhaus T, Hauth J, Nordström K, Trentmann O, Neuhaus EH, Scheuring D, Fehlmann T, Keller A, Simon M, Möhlmann T. 2021. Differential degradation of RNA species by autophagy-related pathways in Arabidopsis. Journal of Experimental Botany 72, 6867–6881 .